The effects of government licensing on e-commerce: Evidence from Alibaba - Ginger Zhe Jin; Zhentong Lu; Xiaolu Zhou; Chunxiao Li (Bank of Canada, 2021)
Using proprietary data from Alibaba, we examine how the 2015 Food Safety Law (FSL) affects e-commerce in China. The FSL requires most food sellers on e-commerce platforms to obtain a valid online license for retail food handling. Because the FSL was rolled out progressively, we have a rare opportunity to observe a gradual transition from voluntary certification to partial licensing and mandatory licensing. Data summary shows that, conditional on sellers with valid licensing information, those that had a better online reputation and more online food sales before the FSL tend to display their FSL license earlier on the platform, and buyers are more willing to transact with a seller after she displays her FSL license. This positive response is stronger for younger and less reputable sellers, suggesting that the license provides useful information in addition to what consumers observe on the platform. To identify the causal impact of the FSL, we compare food and non-food categories via synthetic control matching. We find that the average quality of surviving food sellers has improved after partial and mandatory licensing, partly because those who are unwilling to obtain the FSL license must exit the platform. Despite an increase in seller concentration, the platform's gross merchandise value in the food category did not decline post FSL, nor did the average sales price increase significantly one year into the full enforcement of the FSL. This suggests that the FSL does not hamper the long-run performance of the regulated market, probably because it has enhanced seller quality and market transparency on the platform.
Keywords: D82; K23; L5; L8; 330; Market structure and pricing; Recent economic and financial developments